Feedback Linearization Control for Path Tracking of Articulated Dump Truck - Xuan Zhao; Jue Yang; Wenming Zhang; Jun Zeng (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The articulated dump truck is a widespread tansport vehicle for narrow rough terrain environment. To achieve the autonomous driving in the underground tunnel, this ariticle proporses a path following strategy of articulated vehicle based on feedback linearization algorithm. Fisrt of all, the articulated vehicle kinematics model, which reflects the relationship of the structure parameters and state variables, is established. Refering to the model, the nonlinear errors equation between real path and reference path, which are as the feedback from the path tracking process, is solved and linearized. After estimating the system controllable, according to the error equation, the path following controller with feedback linearization algorithm is designed through calaculating the parameters with the pole assignment. Finally, the hardware in the loop simulation on NI cRIO and PXI controller is lunched for verifying the control quality and real-time path tracking performance.